2020
DOI: 10.5796/electrochemistry.20-00016
|View full text |Cite
|
Sign up to set email alerts
|

Molten Li Salt Solvate-Silica Nanoparticle Composite Electrolytes with Tailored Rheological Properties

Abstract: Nanocomposite electrolytes comprising molten Li salt solvates (MLSs) and inorganic fillers provide liquid-like processing and reasonably high Li ion transport properties. Thus, they can be potentially used as thermally-stable and mechanically-robust electrolytes. In this study, nanocomposite electrolytes exhibiting two distinct non-Newtonian rheological responses, i.e., shear thinning and shear thickening behaviors, were prepared using glyme-and sulfolane-based molten Li salt solvates and hydrophilic fumed sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…10 wt %) but did not change considerably when the content was more than 12.5 wt %. This result indicates that some interactions between ionic liquid and inorganic silica exist, resulting in higher viscosity with a higher silica content, which seems to be consistent with previous reports. ,,, This result showed that the viscosity of the 3D printable precursor mixture composed of inorganic silica, photocurable resin, and ionic liquid can be modulated, and it also suggests that the inks with an appropriate mixing ratio can be used for 3D printing.…”
Section: Resultssupporting
confidence: 91%
“…10 wt %) but did not change considerably when the content was more than 12.5 wt %. This result indicates that some interactions between ionic liquid and inorganic silica exist, resulting in higher viscosity with a higher silica content, which seems to be consistent with previous reports. ,,, This result showed that the viscosity of the 3D printable precursor mixture composed of inorganic silica, photocurable resin, and ionic liquid can be modulated, and it also suggests that the inks with an appropriate mixing ratio can be used for 3D printing.…”
Section: Resultssupporting
confidence: 91%